Financial Distress Analysis as Strategy and Policy Determinants Mining Company - Zarah Puspitaningtyas; Ika Sisbintari; Amalia Muyassaroh (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
Financial distress is the initial condition of company bfore going bankrupt. Financial position is experiencing severe liquidity difficulties, so the company cannot carry out operational activities properly. This study aims to determine the results of assessment of financial distress in mining sector companies listed on BEI for 2015-2019 period as material for determining the company's strategy and policies. This research uses quantitative approach with descriptive analysis method. There are 15 companies as samples based on purposive sampling technique . The analysis technique using Altman Z-Score model. The results showed that there were seven companies experiencing financial distress, five companies experiencing gray area conditions and three companies are declared in non-distress condition . The results of this analysis will be taken into consideration for internal and external parties of the company for making future decisions so that both are profitable